2019
DOI: 10.1111/aas.13465
|View full text |Cite
|
Sign up to set email alerts
|

Clinical examination findings as predictors of acute kidney injury in critically ill patients

Abstract: Background Acute Kidney Injury (AKI) in critically ill patients is associated with a markedly increased morbidity and mortality. The aim of this study was to establish the predictive value of clinical examination for AKI in critically ill patients. Methods This was a sub‐study of the SICS‐I, a prospective observational cohort study of critically ill patients acutely admitted to the Intensive Care Unit (ICU). Clinical examination was performed within 24 hours of ICU admission. The occurrence of AKI was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Nevertheless, healthcare providers can take into account improbable events and take variables that are currently unavailable for algorithms. It remains essential to keep an eye on the patient at the bedside, as previous studies have shown that often simple variables can predict adverse outcomes [ 27 , 28 ]. Furthermore, the healthcare providers' “gut feeling,” or “clinical gestalt,” will probably never be fully understood but may be of crucial additive value.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, healthcare providers can take into account improbable events and take variables that are currently unavailable for algorithms. It remains essential to keep an eye on the patient at the bedside, as previous studies have shown that often simple variables can predict adverse outcomes [ 27 , 28 ]. Furthermore, the healthcare providers' “gut feeling,” or “clinical gestalt,” will probably never be fully understood but may be of crucial additive value.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a very recent study reinforces this hypothesis. Wiersema et al (2020) demonstrated that a prolonged CRT, among other clinical findings, was able to predict AKI development in critically ill patients [ 38 ]. Therefore, new studies are necessary to establish the predictive value of peripheral perfusion assessment for AKI development in septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study flowchart according to the PRISMA statement is shown in Figure 1. The review included 150 studies (encompassing 14.4 million patients) with requisite data to enable sROC curves in 103 studies. The median duration of study data collection was 4 years (range, 3 months to 17 years).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported prospective data collection (124 [82.7%]) . Based on prespecified clinical scenario subgroups, 29 studies assessed AKI associated with nephrotoxic agents, including 26 studies examining radio-contrast medium associated AKI and 3 studies that reported AKI associated with other nephrotoxins; 64 studies assessed AKI prediction in the postoperative setting; 21 studies assessed AKI prediction in intensive care units (ICU); 35 studies assessed AKI in general hospitalizations…”
Section: Resultsmentioning
confidence: 99%